strategi pembiayaan syariah yang berkelanjutan : peran BMT dalam manajemen risiko dan meningkatkan budidaya perikanan di yogyakarta - Putra, Ilham Basrian Jasuma; azizah, isnaini nur azizah; Purnama, Lili (Business Finance Analyst Co., 2024)
This study aims to examine the influence of the factors that influence interest in Islamic venture capital financing. This type of research is descriptive quantitative research data collection using questionnaires distributed directly to respondents. The sampling method uses Hair et al. (2010) where the indicator is multiplied by 5 and obtained as many as 130 respondents, this study shows that cultural factors have a positive and insignificant effect on interest in using Islamic venture capital financing, social factors have a significant positive effect on interest in using Islamic venture capital financing, individual factors have a significant positive effect on interest in using Islamic venture capital financing, each factor that affects interest in Islamic venture capital financing and psychological factors have a positive and insignificant effect on interest in using Islamic venture capital financing. These results are expected to be utilized by parties interested in becoming a source of information and policy-making.